Gold cluster-loaded dendritic nanosilica: single particle luminescence and catalytic properties in the bulk. Issue 21 (24th May 2021) - Mohanty, Jyoti Sarita; Maity, Ayan; Ahuja, Tripti; Chaudhari, Kamalesh; Srikrishnarka, Pillalamarri; Polshettiwar, Vivek; Pradeep, Thalappil
Abstract : A single particle luminescence imaging using the hybrid material, DFNS@AuQC BSA. Abstract : We report a hybrid material in which surface anchoring-induced enhanced luminescence of AuQC @BSA clusters on high surface area dendritic fibrous nanosilica of 800 nm diameter enabled their luminescence imaging at a single particle level. The photophysical and structural properties of the hybrid material were characterized by various spectroscopic and microscopic techniques. Concomitant imaging using scattering and luminescence of such mesostructures and their response to analytes have been used to develop a chemical sensor. The hybrid material was found to be catalytically active in silane to silanol conversion, and 100% conversion was observed in 4 h when the reaction was carried out at 30 °C in the presence of light. Such materials at submicron dimensions with enhanced surface area, emission in the solid state along with a high quantum yield of 12% in water along with enhanced scattering, and surface functionalities present numerous benefits for the creation of multifunctional materials.